Institutional arrangements and rehabilitation of young offenders: a case study of the Leeuwkop correctional service facility. - Macozoma, Mesuli (My University, 2022)
The 1994 democratic transition in South Africa marked a break away from its repressive past, which included the creation of new institutions to exercise the rule of law in a democratic dispensation. Transforming the prison system to correctional services through policy, changed the outlook of the state in exercising punitive measures against those charged with breaking the rule of law. A key question that has emerged is the need to understand how the established correctional services system facilitates the rehabilitation of young offenders, who make the majority of people incarcerated in correctional facilities in South Africa today. The study employed a qualitative case study approach to establish interactions between institutionalised young offenders at Leeuwkop Correctional Service Facility which serves as a medium for rehabilitation. The objective of the study was to determine whether the institutional arrangements at this facility support the institutionalisation of rehabilitation as articulated in the 2005 White Paper on Corrections. Primary data was gathered using semi-structured interviews from a sample of 16 participants, inclusive of three first-time offenders, three repeat offenders, and two former offenders from the Leeuwkop Correctional Service Facility between the ages 21 – 35 years old. In addition, eight institutional actors associated with Leeuwkop Correctional Service Facility were interviewed to understand their perspectives on the administrative processes involved in services offered by the facility. Thematic analysis was employed to analyse the data sets which generated four key themes around the issue of order and discipline, factors contributing to offending, rehabilitation of offenders in a correctional environment, and the allocation and expenditure of financial resources. Research findings indicate that a lack of transformation and misalignment of the current institutional arrangements is obscuring effective rehabilitation of young offenders at Leeuwkop Correctional Service Facility. A significant finding that emerged was that the primary objective of the Leeuwkop Correctional Service Facility is the incarceration of young offenders, and rehabilitation is a secondary function; hence the institutional and structural arrangements emphasize achieving the primary goal Conditions at Leeuwkop Correctional Service Facility, reveal that institutions established with contradicting mandates tend to systematically resist change. Arguably, the institution has struggled to transform its secondary role into an actionable goal that aligns with the policy framework, rendering this space a constitutive element in engendering a vicious cycle of violence among those who interact with the institution. The research concludes that more work is needed at both institutional and administrative level to foster a culture of rehabilitation within correctional service facilities.
A research report submitted in partial fulfilment of the requirements for the Degree of Master of Management in the Field of Public Policy at the Faculty of Commerce, Law and Management, School of Governance, University of the Witwatersrand, 2021
Keywords: UCTD; Rehabilitation; Young Offenders; Correctional Service; Law; SDG-16: Peace, justice and strong institutions